The Combination Effect of Purpureocillium lilacinum Strain (AUMC 10620) and Avermectin (B1a and B1b) on Control Citrus Nematode Tylenchulus semipenetrans (Cobb) Under Laboratory and Field Conditions - Amr M. El-Marzoky; Mohamed A. M. S. Ali; Ahmed S. M. Elnahal; Dalia A. Abuljadayel; Wafa A. H. Alkherb; Mahmoud Moustafa; Mohammed O. Alshaharni; Elsayed M. Abd El-Aal (Biology)
This study investigates the nematicidal efficacy of Purpureocillium lilacinum strain (AUMC 10620) combined with avermectin (B1a and B1b) against the citrus nematode Tylenchulus semipenetrans, both in vitro and in vivo. Laboratory experiments tested four concentrations of P. lilacinum (2.5, 5, 10, and 15 × 107 spores/mL) mixed with 250 ppm avermectin, assessing their effects on nematode juveniles (J2) and eggs. Results showed significant increases in juvenile mortality and egg hatching inhibition with the combined treatments compared to individual applications. The highest concentration (15 × 107 spores/mL + 250 ppm avermectin) achieved 100% juvenile mortality and 83.33% egg hatching inhibition after 72 h. Field trials confirmed the superior efficacy of the combined treatment, with P. lilacinum (15 × 107 spores/mL) and avermectin (1000 ppm) reducing nematode populations by 70.85% in mandarin trees and 70.77% in sweet orange trees after three weeks, compared to the 83.59% and 81.76% reduction, respectively, achieved by oxamyl. These findings suggest that mixtures of P. lilacinum and avermectin can serve as effective, eco-friendly alternatives for controlling nematodes in citrus orchards.